Educação ambiental, intercultura e antropofagia cultural brasileira contribuições para a formação de professores (as) - Silva, Ivete Souza da (2010)
The present research that I bring as Masters Degree Dissertation in Education, in the Line Professional Formation, Knowledge and Development (PPGE-UFSM), aims to contribute with theoretical and epistemological subsidies for Formation of Teachers in general, and for the Environmental Education in particular, based on assumptions of the Brazilian Cultural Anthropophagy, in an intercultural perspective. For the development of this Masters Degree Dissertation, activities of qualitative research and of theoretical-bibliographic character were carried out. The reference that guided the investigative and reflective gaze of the researcher (BARCELOS, 2005) in the sense of the production of the research information (JACQUES GAUTHIER, 1998), was the establishment of dialogues that could privilege the intercultural aspects (CANCLINI, 2003a) with imaginaries and representations about environmental issues and the formation of teachers, present in the production of cultural anthropophagic orientation, post Modern Art Week of 1922. The relevance of this research is the search for alternatives to deal with the challenges posed to education due to the drastic changes occurring in the world today. The need for coexistence between the various has provided a centering of cultural identities. The meetings and/or clashes between cultures do not occur in a simple manner, and the school, as one of the areas of socialization, is related to this process. In this way it was intended, through the dialogue between authors in the areas of Formation of Teachers, Environmental Education, Interculture and Brazilian Cultural Anthrophagy, to answer the following research problem: How the propositions of the Brazilian Cultural Anthropophagy can contribute to the Formation of Teachers in general, and to the Environmental Education in particular, in an intercultural perspective? Thus, answering to the question that brought me here, I state that: the anthropophagic propositions contribute as inviting to all to the creation and to the dialogue through the devouring, breaking with the idea of imitation and copy.